2023
DOI: 10.1111/sed.13147
|View full text |Cite
|
Sign up to set email alerts
|

The thickness variability of fluvial cross‐strata as a record of dune disequilibrium and palaeohydrology proxy: A test against channel deposits

Luca Colombera,
Arnold J. H. Reesink,
Robert A. Duller
et al.

Abstract: Strata produced by fluvial dunes can provide insight into the hydrological regime of ancient rivers. Recent experiments indicate that conditions of disequilibrium between bedforms and formative flows may be inferred from the coefficient of variation of preserved dune cross‐set thickness, suggesting that this quantity may act as a proxy for the flashiness of river floods relative to the time required for full bedform translation. To assess whether this idea is applicable to interpretations of the stratigraphic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
1
1
0
Order By: Relevance
“…Together, these results provide a mechanistic basis for the findings of Colombera et al. (2024), who, in their meta‐analysis of modern river deposits, identified a lack of correlation between T f normalized by trueTt,H $\overline{{T}_{t,H}}$ and preserved set thickness. This lack of correlation can be indicative of varying degrees of flood signal degradation, where floods with trueTt,H<Tf<trueTt,L $\overline{{T}_{t,H}}< {T}_{f}< \overline{{T}_{t,L}}$ have a lower degradation potential than Tf<trueTt,H ${T}_{f}< \overline{{T}_{t,H}}$, and only floods with Tf>trueTt,L ${T}_{f} > \overline{{T}_{t,L}}$ are expected to be minimally degraded (Figure 2).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Together, these results provide a mechanistic basis for the findings of Colombera et al. (2024), who, in their meta‐analysis of modern river deposits, identified a lack of correlation between T f normalized by trueTt,H $\overline{{T}_{t,H}}$ and preserved set thickness. This lack of correlation can be indicative of varying degrees of flood signal degradation, where floods with trueTt,H<Tf<trueTt,L $\overline{{T}_{t,H}}< {T}_{f}< \overline{{T}_{t,L}}$ have a lower degradation potential than Tf<trueTt,H ${T}_{f}< \overline{{T}_{t,H}}$, and only floods with Tf>trueTt,L ${T}_{f} > \overline{{T}_{t,L}}$ are expected to be minimally degraded (Figure 2).…”
Section: Discussionsupporting
confidence: 68%
“…We anticipate this prolonged transition to the white-noise regime in preserved deposition rates because scours bracketing bedform groups can cause hiatuses in the preserved record, spanning multiple bedform-group turnover timescales. Together, these results provide a mechanistic basis for the findings of Colombera et al (2024), who, in their meta-analysis of modern river deposits, identified a lack of correlation between T f normalized by T t,H and preserved set thickness. This lack of correlation can be indicative of varying degrees of flood signal degradation, where floods with T t,H < T f < T t,L have a lower degradation potential than T f < T t,H , and only floods with T f > T t,L are expected to be minimally degraded (Figure 2).…”
Section: Discussionmentioning
confidence: 53%